Tip60 is associated with resistance to X‐ray irradiation in prostate cancer. Issue 2 (28th December 2017) - Xie, Xin; Xu, Zhaoping; Wang, Chenghe; Fang, Chen; Zhao, Juping; Xu, Le; Qian, Xiaoqiang; Dai, Jun; Sun, Fukang; Xu, Danfeng; He, Wei
Abstract : Tip60, an oncogene, accelerates cell growth by regulating androgen receptor translocation into the nucleus in prostate cancer. However, the mechanism of Tip60 in the response of prostate cancer to radiotherapy, and radioresistance, has not been studied. Using human prostate cancer samples and two human prostate cancer cell lines (LNCaP and DU145), Tip60 protein expression and the acetylation of ataxia telangiectasia mutant (ATM) were analysed by western blotting and immunoprecipitation. Tip60 was downregulated with small interfering RNA. Cells were irradiated using X‐rays at 0.25 Gy·min −1 . Cell viability was assessed by the MTT assay. The expression of Tip60 protein was increased in radioresistant prostate cancer tissues in comparison with radiosensitive tissues, which was also confirmed in both irradiated DU145 and LNCaP cells. Furthermore, the acetylation of ATM was also upregulated in a time‐dependent manner after irradiation of both DU145 and LNCaP cells. Additionally, depletion of Tip60 decreased the survival of LNCaP and DU145 cells by inducing apoptosis, reduced the acetylation of ATM and decreased the expression of phosphorylated ATM, Chk2 and cdc25A in both DU145 and LNCaP cells after X‐ray irradiation. The results of this study demonstrated that the expression of Tip60 may be related to the radioresistance of prostate cancer and could serve as a promising predictive factor for prostate cancer patients receiving radiotherapy. Abstract : Tip60 in prostate cancer, upregulated by radiotherapy, could increase the expression of acetylation of ataxia telangiectasia mutant (ATM). On the one hand, acetylated ATM mediated cell cycle by increasing the phosphorylation of Chk2, dc25A. On the other hand, acetylated ATM affected expression of apoptosis‐related molecular markers, including Bcl‐1, cleaved caspase 3 and cytochrome C.